2013
DOI: 10.1093/infdis/jit083
|View full text |Cite
|
Sign up to set email alerts
|

Improved Pregnancy Outcomes in Women Exposed to Malaria With High Antibody Levels Against Plasmodium falciparum

Abstract: Antiparasite IgGs in women at delivery are affected by HIV infection, as well as by variations in the exposure to P. falciparum. Heterogeneity of malaria transmission needs to be considered to identify IgGs against VAR2CSA and other parasite antigens associated with improved pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 48 publications
5
38
1
Order By: Relevance
“…Again, previous malaria episodes have been demonstrated to be associated with increased antibody levels [59] but this was not explored in the present study. Another interesting factor associated with failure to acquire protective PAM immunity is exposure-reducing interventions [41].…”
Section: Discussionmentioning
confidence: 94%
“…Again, previous malaria episodes have been demonstrated to be associated with increased antibody levels [59] but this was not explored in the present study. Another interesting factor associated with failure to acquire protective PAM immunity is exposure-reducing interventions [41].…”
Section: Discussionmentioning
confidence: 94%
“…The interaction between malaria and HIV is particularly deleterious in pregnant women, leading to increased risk and severity of both malaria infection and disease [1],[2]. In addition, HIV infection attenuates the relative protection against malaria acquired with subsequent pregnancies, placing more women at risk for malaria-related complications [4],[5]. Moreover, HIV infection reduces the efficacy of malaria interventions and complicates the use of antimalarials because of potential drug interactions [6],[7].…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports the mothers were secundigravidae [9], secundigravidae with placental malaria and HIV [41] or women with chronic placental infection [35] and antibody levels were measured at delivery rather than in early pregnancy. Rather than demonstrating population-wide associations between malaria antibodies and birthweight (as studied here), most published studies have been restricted to women of a specific gravidity or HIV and/or malaria infection status [12, 30, 33]. Further prospective studies of these high-risk groups for associations between immunity and outcome may be indicated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, malaria infection, HIV and gravidity have been shown to modify the effects of the association between malaria immunity and pregnancy outcomes [12, 23]. Malaria prevention strategies such as indoor residual spraying, insecticide-treated bed nets (ITNs) and intermittent preventive treatment in pregnancy (IPTp) are designed to reduce the exposure to malaria and improve pregnancy outcomes, but may impair acquisition of immunity [24].…”
Section: Introductionmentioning
confidence: 99%